2014
DOI: 10.1371/journal.pone.0089924
|View full text |Cite
|
Sign up to set email alerts
|

Laccase Catalyzed Synthesis of Iodinated Phenolic Compounds with Antifungal Activity

Abstract: Iodine is a well known antimicrobial compound. Laccase, an oxidoreductase which couples the one electron oxidation of diverse phenolic and non-phenolic substrates to the reduction of oxygen to water, is capable of oxidizing unreactive iodide to reactive iodine. We have shown previously that laccase-iodide treatment of spruce wood results in a wash-out resistant antimicrobial surface. In this study, we investigated whether phenolic compounds such as vanillin, which resembles sub-structures of softwood lignin, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 53 publications
2
35
0
2
Order By: Relevance
“…These results suggest an important role for apoplastic H 2 O 2 in extracellular lignin production. Moreover, as iodide does not inhibit laccase activity in vitro (Ihssen et al, 2014), the results suggest that peroxidases are crucial for monolignol oxidation during extracellular lignin formation. To investigate the effects of apoplastic H 2 O 2 scavenging on phenolic metabolism, a time-course sampling of cells and culture medium from the various types of culture (Supplemental Fig.…”
mentioning
confidence: 75%
“…These results suggest an important role for apoplastic H 2 O 2 in extracellular lignin production. Moreover, as iodide does not inhibit laccase activity in vitro (Ihssen et al, 2014), the results suggest that peroxidases are crucial for monolignol oxidation during extracellular lignin formation. To investigate the effects of apoplastic H 2 O 2 scavenging on phenolic metabolism, a time-course sampling of cells and culture medium from the various types of culture (Supplemental Fig.…”
mentioning
confidence: 75%
“…Antioxidant, antitumor, and anti-depressive compounds have been synthesized using this enzyme [8][9][10][11] . Additionally, this enzyme has been recently used for the synthesis of antifungal compounds 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In an innovative and seminal research, Schubert et al (2012) and Ihssen et al (2014) demonstrated that KI could be bound to wood using the laccase-mediator system. In this way, KI would then provide antimicrobial surfaces even after leaching.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, KI would then provide antimicrobial surfaces even after leaching. The research of Schubert et al (2012) and Ihssen et al (2014) was some of the first to be conducted which demonstrated a new and bio-based technology to fix iodine residues onto Norway spruce wood for potential protection in a safe and environmentally acceptable manner. Their work was focused on wood rather than bamboo or grasses but demonstrated the effectiveness of such treatments against a wide variety of fungi including blue-stain, wood decay, yeasts, and gram-positive and gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%